Temporal Variations in Water Quantity and Quality of Orontes River, Turkey - ODEMIS, BERKANT; KEMAL SANGUN, MUSTAFA; BUYUKTAS, DURSUN (Asian Journal of Chemistry, 2010)
The aim of this study was to determine variations in physical and chemical water quality parameters of the Turkish part of Orontes River, whose basin is shared by Lebanon, Syria and Turkey, between 1984 and 2002. Due to very low amount of surface water in the region, groundwater is densely used for irrigation. In this case, it causes an increase in the salinity in some regions of Amik Plain, Hatay, Turkey. As a result of extensive usage of the river for irrigation in the region, the flow rate has decreased significantly. The most important impairment in flow rate occurred in 2000. The value of EC and pH were found to be relatively low in the year of 1984 and then found to increase in 2002. OM level showed a decreasing trend between the years of 1984 and 1992. The total boron content showed yearly periodic cycles and generally had a decreasing trend. The river has a notably fluctuating flow rate and the amount of water varies seasonally. According to the long-term data, the flow rate was falling to an average value of 3.66 m3s-1 in August. Organic pollutant parameters (TDS, BOD and COD) fluctuated at rainy, transitional and dry seasons. Between 1999 and 2001, TDS and COD values showed an increasing trend, while BOD levels showed a decreasing trend.